Hydrogeochemical Assessment and Identification of Controlling Factors of Chemical Composition of Spring Waters in Alashtar Plain, Lorestan Province - Vahab Amiri (تحقیقات کاربردی علوم جغرافیایی)
In this study, the hydrogeochemical status of groundwater resources is evaluated using chemical analysis of 346 samples supplied from 10 springs. Based on Gibbs and van Wirdum diagrams, interaction with rock and sedimentary formations is the dominant process of controlling water chemistry. Based on the Chadha diagram and output of AquaChem program, the amount of alkali earth elements (Ca and Mg) is more than alkali ones (Na and K) and the value of weak acidic anions (CO3 and HCO3) is more than strong acidic anions (Cl and SO4). Therefore, the dominant hydrochemical facies in water samples are Ca-Mg-HCO3 and Mg-Ca-HCO3. In this plain, carbonate and probably halite dissolution are the causes of Ca, HCO3 and Cl abundance in water samples. All samples showed the HCO3+SO4 of less than 5 meq/l and demonstrate that the dominant process affecting water chemistry is the calcite and dolomite dissolution. Ion exchange between fine-grained materials of the aquifer and water solution has occurred very vastly. Based on chloroalkalin (I, II) indices, about 5.49% of samples exhibited the reverse ion exchange. Calculation of the saturation index showed that all samples are undersaturated with respect to anhydrite, aragonite, calcite, dolomite, gypsum, and CO2. Besides, the saturation index of water samples for calcite and aragonite is greater than anhydrite, dolomite, and gypsum. Analysis of principal components affecting water chemistry showed that about 82% of changes in water chemistry is controlled by 4 factors which factor 1 including Ca and HCO3, factor 2 including Na and Cl, factor 3 including Mg and SO4 and finally factor 4 including pH.